Pengungkapan Corporate Social Responbility terhadap Tax Aggressiveness - Dwi Lestari; Ely Kartikaningdyah (Pusat P2M Politeknik Negeri Batam, 2019)
The aim of this study is to examine the effect of corporate social responsibility (CSR) to corporate tax aggressiveness. The independent variable is used in this study is corporate social responsibility disclosure.While the dependent variable in this study is tax aggressiveness that measured using two effective tax rates measures. This study is a replication of and use 151 manufacturing companies that listed on the Indonesia Stock Exchange as the sample. Samples were selected by purposive sampling method and finally obtained 62 manufacturing companies per year that fulfill the criterias. Data were analyzed using ordinary least square regression analysis model. The result shows that the higher the level of CSR disclosure of a corporation, the higher is the level of tax aggressiveness.